Preparation method of polyimide coating
By treating the polyamic acid solution coating in low-humidity and high-humidity environments, forming a rough surface and imidizing it, the problem of difficult interface processing of polyimide materials is solved, and the interface bonding strength of composite materials is improved.
Patent Information
- Application Number
- CN202411493251.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
Polyimide materials have low surface energy and poor surface affinity, which leads to difficult handling of interface problems. The existing roughening treatment methods are difficult to control, affecting the performance of the coating.
Polyimide coatings are prepared by leveling drying in a low humidity environment, then storing in a high humidity environment to evaporate the coating solvent to form a rough surface, and finally imidizing the treatment.
It realizes efficient roughening treatment of polyimide coating, simple process and strong applicability, and improves the interface bonding strength of composite materials.
Smart Images

Figure CN119456367A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and particularly relates to a method for preparing a polyimide coating. Background Art
[0002] Polyimide is a polymer material with imide ring as the structural unit. It has excellent mechanical properties, heat resistance, thermal stability, insulation, etc., and is therefore widely used in aerospace, electronics and electrical fields. Polyimide materials have low surface energy and poor surface affinity, so the treatment of interface problems has always been a challenge in the preparation of composite materials containing polyimide coatings.
[0003] Solutions to polyimide interface problems are mainly divided into chemical modification and surface roughening. In order to maximize the improvement of interface performance, the two surface treatment methods are usually used at the same time. The surface roughening treatment methods are divided into two types: before and after resin imidization. After the imidization of the polyamic acid resin coating, grinding, sandblasting, and chemical etching are usually used to create a rough surface. Due to the high strength of the polyimide resin, the roughening treatment after imidization is usually difficult to control and has a great damage to the coating performance. The treatment before polyimide imidization generally adopts the method of adding filler particles to the resin or using a template. The former usually affects the mechanical, dielectric and other properties of the film, while the latter has more application restrictions and is difficult to apply to curved surfaces.
[0004] Therefore, developing a method for roughening the surface of polyimide coatings with a simple process and little damage to the coating, and improving the interfacial bonding strength of composite materials containing polyimide, is one of the research focuses in this field. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for preparing a polyimide coating.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a polyimide coating comprises the following steps:
[0008] In the first step, a conventional coating preparation method is used to evenly cover a certain concentration of polyamic acid solution on the surface of the substrate under low humidity conditions, and the substrate coated with the polyamic acid solution coating is placed in this environment for leveling and drying for a certain period of time.
[0009] In the second step, the substrate coated with the polyamic acid solution coating is moved to a high humidity environment and stored in this high humidity environment for a certain period of time to evaporate the solvent. During this process, as the solvent evaporates, the side of the coating in contact with the air changes from a smooth surface to a rough surface.
[0010] In the third step, the substrate coated with the polyamic acid solution coating is moved to a curing device for imidization treatment to obtain a polyimide coating with a rough surface.
[0011] Furthermore, the low humidity environment condition is humidity ≤ 50%, 10° C. ≤ temperature ≤ 50° C. Preferably, humidity ≤ 35%, 25° C. ≤ temperature ≤ 35° C.
[0012] Furthermore, the leveling drying time in the low humidity environment is 1 to 60 minutes.
[0013] Furthermore, the storage time in the high humidity environment is not less than 120 minutes, until most of the solvent evaporates and the coating solution has no fluidity.
[0014] Furthermore, the high humidity environment condition is humidity ≥ 50%, 10° C. ≤ temperature ≤ 50° C. Preferably, humidity ≥ 70%, 10° C. ≤ temperature ≤ 35° C.
[0015] Furthermore, the polyamic acid solution comprises aromatic diamine monomers, aromatic dianhydride monomers and a solvent, and the molar ratio of the aromatic dianhydride monomers to the aromatic diamine monomers is 0.95-1.05:1.
[0016] Furthermore, the aromatic diamine is 4,4-diaminodiphenyl ether, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4-diaminobiphenyl, p-phenylenediamine, 3,4-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diaminodiphenyl sulfone, 3,3'-dimethyl-4,4-diaminobiphenyl, 3,3'-diamino-benzophenone, 4,4'-diamino-benzophenone, 2,2 At least one of '-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-diaminobenzanilide, 2,2'-bis(4-aminophenyl)hexafluoropropane, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene and 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
[0017] Further, the aromatic dianhydride is at least one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, pyromellitic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4-hexafluoroisopropylphthalic anhydride, 2,3,3',4',-biphenyltetracarboxylic dianhydride, 2,3,3',4',-diphenyl ether tetracarboxylic dianhydride and 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride).
[0018] Furthermore, the solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.
[0019] Furthermore, the concentration of the polyamic acid solution is 3wt% to 45wt%.
[0020] Furthermore, the substrate includes one of a resin-based composite material, a ceramic-based composite material, glass, and a metal.
[0021] Furthermore, the imidization treatment is performed by heating the temperature to 330-390° C. for 3 to 60 minutes.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] The existing methods for preparing rough polyimide coatings are usually chemical etching, physical sandblasting, grinding, etc., which are highly destructive and have poor process applicability. The present invention innovatively prepares a polyimide coating with a certain degree of roughness by controlling humidity. This method has the characteristics of high efficiency, simple process method, strong process applicability, no introduction of additional additives or fillers, and no introduction of additional templates. It can be applied to the aerospace field to prepare composite materials with high interface bonding performance and can improve the interface bonding strength of composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flow chart of the steps of the method for preparing the polyimide coating of the present invention. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below through specific embodiments.
[0026] Example 1
[0027] Step 1: Mix pyromellitic anhydride, 4,4-diaminodiphenyl ether and N,N-dimethylacetamide evenly, and then react at 10°C for 24 hours to obtain a polyamic acid solution, wherein the molar ratio of pyromellitic anhydride to 4,4-diaminodiphenyl ether is 0.98:1. The total content of pyromellitic anhydride and 4,4-diaminodiphenyl ether is 15wt%.
[0028] Step 2: In an environment with a humidity of 35% and a temperature of 30° C., the polyamic acid solution obtained in the above step is evenly coated on the surface of a glass plate with a thickness of 2 mm, and allowed to stand in this environment for 30 minutes.
[0029] Step 3: Move the glass plate coated with the polyamic acid solution into a constant temperature and humidity environment box with a humidity of 95% and a temperature of 30°C. Leave it in this environment for 480 minutes.
[0030] Step 4: Put the glass plate coated with the polyamic acid solution in the previous step into an oven, heat the oven to 375°C, and imidize for 30 minutes to obtain a polyimide coating with a rough surface, and the surface roughness of the coating is 3.2.
[0031] Example 2
[0032] The first step: 4,4-hexafluoroisopropylphthalic anhydride, 3,4-diaminodiphenyl ether and N-methylpyrrolidone are mixed evenly, and then reacted at 10°C for 48 hours to obtain a polyamic acid solution, wherein the molar ratio of 4,4-hexafluoroisopropylphthalic anhydride to 3,4-diaminodiphenyl ether is 1:1. The total content of 4,4-hexafluoroisopropylphthalic anhydride and 3,4-diaminodiphenyl ether is 5wt%.
[0033] Step 2: In an environment with a humidity of 35% and a temperature of 30° C., the polyamic acid solution obtained in the above step is evenly sprayed on the surface of an iron sheet with a thickness of 0.5 mm, and allowed to stand in this environment for 10 minutes.
[0034] Step 3: Move the iron sheet sprayed with the polyamic acid solution to a constant temperature and humidity environment box with a humidity of 65% and a temperature of 35° C. Leave it in this environment for 480 minutes.
[0035] Step 4: Put the iron sheet sprayed with the polyamic acid solution in the previous step into an oven, heat the oven to 375°C, and imidize for 30 minutes to obtain a polyimide coating with a rough surface, and the surface roughness of the coating is 1.2.
[0036] Example 3
[0037] Step 1: Evenly mix pyromellitic anhydride, 4,4-diaminodiphenyl ether and solvent (a 1:1 mixed solution of N,N-dimethylacetamide and N-methylpyrrolidone), and then react at 10°C for 24 hours to obtain a polyamic acid solution, wherein the molar ratio of pyromellitic anhydride to 4,4-diaminodiphenyl ether is 0.99:1. The total content of pyromellitic anhydride and 4,4-diaminodiphenyl ether is 15wt%.
[0038] Step 2: In an environment with a humidity of 40% and a temperature of 35°C, the polyamic acid solution obtained in the above step is evenly coated on the surface of a 2 mm thick polyarylacetylene / quartz fiber composite material plate, and allowed to stand in this environment for 10 minutes.
[0039] Step 3: Move the polyarylacetylene / quartz fiber composite material plate coated with the polyamic acid solution into a constant temperature and humidity environment box with a humidity of 90% and a temperature of 30° C. Leave it in this environment for 120 minutes.
[0040] Step 4: Place the polyarylacetylene / quartz fiber composite material plate coated with the polyamic acid solution in the previous step into an oven, heat the oven to 375°C, and imidize for 30 minutes to obtain a polyimide coating with a rough surface, and the surface roughness of the coating is 12.1.
[0041] Example 4
[0042] Step 1: Mix pyromellitic anhydride, 4,4-diaminodiphenyl ether and N,N-dimethylacetamide evenly, and then react at 10°C for 24 hours to obtain a polyamic acid solution, wherein the molar ratio of pyromellitic anhydride to 4,4-diaminodiphenyl ether is 0.96:1. The total content of pyromellitic anhydride and 4,4-diaminodiphenyl ether is 25wt%.
[0043] Step 2: In an environment with a humidity of 35% and a temperature of 40° C., the polyamic acid solution obtained in the above step is evenly coated on the surface of a glass plate with a thickness of 2 mm, and allowed to stand in this environment for 30 minutes.
[0044] Step 3: Move the glass plate coated with the polyamic acid solution to a constant temperature and humidity environment box with a humidity of 60% and a temperature of 30°C. Leave it in this environment for 480 minutes.
[0045] Step 4: Put the glass plate coated with the polyamic acid solution in the previous step into an oven, heat the oven to 375° C., and imidize for 30 minutes to obtain a polyimide coating with a rough surface, and the surface roughness of the coating is 0.6.
[0046] Comparative Example 1:
[0047] The first step: mixing pyromellitic anhydride, 4,4-diaminodiphenyl ether and N,N-dimethylacetamide evenly, and then reacting at 10°C for 24 hours to obtain a polyamic acid solution, wherein the molar ratio of pyromellitic anhydride to 4,4-diaminodiphenyl ether is 0.99:1; the total content of pyromellitic anhydride and 4,4-diaminodiphenyl ether is 15wt%.
[0048] Step 2: In an environment with a humidity of 35% and a temperature of 30° C., the polyamic acid solution obtained in the above step is evenly coated on the surface of a glass plate with a thickness of 2 mm, and allowed to stand in this environment for 300 minutes.
[0049] Step 3: Move the glass plate coated with the polyamic acid solution to a constant temperature and humidity environment box with a humidity of 80% and a temperature of 30°C. Leave it in this environment for 480 minutes.
[0050] Step 4: Put the glass plate coated with the polyamic acid solution in the previous step into an oven, heat the oven to 375°C, and imidize for 30 minutes to obtain a polyimide coating with a surface roughness of 0.05.
[0051] Comparative Example 2:
[0052] The first step: mixing pyromellitic anhydride, 4,4-diaminodiphenyl ether and N,N-dimethylacetamide evenly, and then reacting at 10°C for 24 hours to obtain a polyamic acid solution, wherein the molar ratio of pyromellitic anhydride to 4,4-diaminodiphenyl ether is 0.99:1; the total content of pyromellitic anhydride and 4,4-diaminodiphenyl ether is 15wt%.
[0053] Step 2: In an environment with a humidity of 35% and a temperature of 30° C., the polyamic acid solution obtained in the above step is evenly coated on the surface of a glass plate with a thickness of 2 mm, and allowed to stand in this environment for 100 minutes.
[0054] Step 3: Move the glass plate coated with the polyamic acid solution to a constant temperature and humidity environment box with a humidity of 70% and a temperature of 45°C. Leave it in this environment for 60 minutes.
[0055] Step 4: Put the glass plate coated with the polyamic acid solution in the previous step into an oven, heat the oven to 375°C, and imidize for 30 minutes to obtain a polyimide coating with a surface roughness of 0.09.
[0056] Comparative Example 3:
[0057] The first step: mixing pyromellitic anhydride, 4,4-diaminodiphenyl ether and N,N-dimethylacetamide evenly, and then reacting at 10°C for 24 hours to obtain a polyamic acid solution, wherein the molar ratio of pyromellitic anhydride to 4,4-diaminodiphenyl ether is 0.99:1; the total content of pyromellitic anhydride and 4,4-diaminodiphenyl ether is 15wt%.
[0058] Step 2: In an environment with a humidity of 35% and a temperature of 30° C., the polyamic acid solution obtained in the above step is evenly coated on the surface of a glass plate with a thickness of 2 mm, and allowed to stand in this environment for 480 minutes.
[0059] Step 3: Put the glass plate coated with the polyamic acid solution in the previous step into an oven, heat the oven to 375°C, and imidize for 30 minutes to obtain a polyimide coating with a surface roughness of 0.04.
[0060] The surface roughness of the polyimide coatings prepared in the above-mentioned embodiments and comparative examples is shown in Table 1. In Examples 1-4 of the polyimide coating preparation method of the present invention, when the wet film of the coating made of the polyamic acid solution is exposed to high humidity air, the water molecules in the air dissolve in the coating, resulting in a change in the solubility of the polyamic acid molecules in the coating, partial agglomeration of the molecules, and formation of a rough structure after the solvent evaporates, thereby significantly improving the surface roughness of the polyimide coating, and further facilitating the improvement of the interface bonding strength of the composite material containing polyimide. Comparative Examples 1-3 are placed in a low humidity environment in a wet film state, during which the solvent evaporates to form a dry film, and thereafter the humid air is difficult to have an impact, resulting in a lower roughness of the coating.
[0061] Table 1
[0062]
[0063]
[0064] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A method for preparing a polyimide coating, characterized in that: The following steps are involved: Under low humidity conditions, the polyamic acid solution is evenly covered on the surface of the substrate and leveled and dried for a certain period of time; The substrate coated with the polyamic acid solution coating is moved to a high humidity environment and stored in the high humidity environment for a certain period of time to evaporate the solvent, and during the evaporation of the solvent, the side of the coating in contact with the air is transformed from a smooth surface to a rough surface; The substrate coated with the polyamic acid solution coating is moved to a curing device for imidization treatment to obtain a polyimide coating with a rough surface.
2. The method according to claim 1, characterized in that The low humidity environment conditions are humidity ≤ 50%, and temperature 10°C ≤ ≤ 50°C.
3. The method according to claim 1, characterized in that The leveling drying time is 1 to 60 minutes.
4. The method according to claim 1, characterized in that: The step of storing the solvent in a high humidity environment for a certain period of time to volatilize the solvent is performed, wherein the storage time is not less than 120 minutes.
5. The method according to claim 1, characterized in that The high humidity environment conditions are humidity ≥ 50%, and temperature 10°C ≤ ≤ 50°C.
6. The method according to claim 1, characterized in that The polyamic acid solution comprises aromatic diamine monomers, aromatic dianhydride monomers and a solvent, and the molar ratio of the aromatic dianhydride monomers to the aromatic diamine monomers is 0.95-1.05:
1.
7. The method according to claim 6, characterized in that The aromatic diamines are 4,4-diaminodiphenyl ether, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4-diaminobiphenyl, p-phenylenediamine, 3,4-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diaminodiphenyl sulfone, 3,3'-dimethyl-4,4-diaminobiphenyl, 3,3'-diamino-benzophenone, 4,4'-diamino-benzophenone, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-diaminobenzanilide, 2,2'-bis(4-aminophenyl)hexafluoropropane, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenyl)hexafluoropropane] The aromatic dianhydride is at least one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, pyromellitic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4-hexafluoroisopropylphthalic anhydride, 2,3,3',4',-biphenyltetracarboxylic dianhydride, 2,3,3',4',-diphenyl ether tetracarboxylic dianhydride and 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride).
8. The method according to claim 6, characterized in that The solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; the concentration of the polyamic acid solution is 3wt% to 45wt%; and the substrate includes one of a resin-based composite material, a ceramic-based composite material, glass, and a metal.
9. The method according to claim 1, characterized in that: The imidization treatment is performed by heating the temperature to 330-390° C. for 3-60 minutes.
10. The polyimide coating prepared according to the method according to any one of claims 1 to 9.